Intravenous thrombolysis for acute ischemic stroke in Greece: the Safe Implementation of Thrombolysis in Stroke registry 15-year experience. (26th June 2018) - Tsivgoulis, Georgios; Kargiotis, Odysseas; Rudolf, Jobst; Komnos, Apostolos; Tavernarakis, Antonios; Karapanayiotides, Theodoros; Ellul, John; Katsanos, Aristeidis H.; Giannopoulos, Sotirios; Gryllia, Maria; Safouris, Apostolos; Papamichalis, Panagiotis; et al.
Background: Intravenous thrombolysis (IVT) remains the only approved systemic reperfusion treatment for acute ischemic stroke (AIS), however there are scarce data regarding outcomes and complications of IVT in Greece. We evaluated safety and efficacy outcomes of IVT for AIS in Greece using the Safe Implementation of Thrombolysis in Stroke: International Stroke Thrombolysis Register (SITS-ISTR) dataset. Methods: All AIS patients treated with IVT in Greece between December 2002 and July 2017 and recorded in the SITS-ISTR were evaluated. Demographics, risk factors, baseline stroke severity [defined using National Institutes of Health Stroke Scale (NIHSS)], and onset-to-treatment time (OTT) were recorded. Safety outcomes included symptomatic intracranial hemorrhage (sICH) and 3-month mortality rates. The efficacy outcomes evaluated a reduction in baseline NIHSS score at 2 and 24 h following IVT onset, 3-month favorable functional outcome [FFO; modified Rankin scale (mRS) scores of 0–1] and 3-month functional independence (FI; mRS-scores of 0–2). The safety and efficacy outcomes were assessed comparatively with previously published data from SITS national and international registries. Results: A total of 523 AIS patients were treated with IVT in 12 Greek centers participating in the SITS-ISTR during the study period (mean age 62.4 ± 12.7; 34.6% women; median baseline NIHSS score: 11 points; median OTT: 150 min). The rates of sICH were 1.4%, 2.3%, and 3.8% according to the SIST-MOST, ECASS II, and NINDS criteria respectively. The median reduction in NIHSS score at 2 and 24 h was 3 [interquartile range (IQR): 1–5] and 5 (IQR: 2–8) points respectively. The 3-month FI, FFO and mortality were 66.5%, 55.6% and 7.9%. All safety and efficacy outcomes were comparable with available data from SITS-ISTR in other European countries. Conclusions: Our study underscores the safety and efficacy of IVT for AIS in Greece. Additional action is necessary in order to increase the availability of IVT in the Greek population and to include more centers in the SITS-ISTR.